Irritation, Impudence, Insight: A Critical Reading of Knut Hamsun’s På turné - Kruszelnicki, Michał (Nordlit, 2010)
The article brings the critical reading of Knut Hamsun’s På turné – the collection of Hamsun’s three polemic lectures entitled: “Norsk litteratur”, “Psykologisk litteratur” and “Modelitteratur”. These texts make up Hamsun’s theoretical and literary manifesto (1891), which up to the present has remained an important introduction to his early and most acclaimed work. In two first sections of the text I follow Hamsun’s scornful arguments against Norwegian realistic literature (as represented mainly by “the great four” writers: Bjørnson, Ibsen, Lie and Kielland) in an attempt to concisely present Hamsun’s reformatory plan according to which Norwegian literature should be freed from its entanglement in didacticism and social bias and redirected onto a path of a deeper psychology. The final part of the article presents a critical assessment of Hamsun’s endeavor. I believe some of Hamsun’s opinions in the matter of literature are still up-to-date and thoughtprovoking. These insights, however, have to be separated from Hamsun’s hasty generalizations concerning the work of Bjørnson, Lie, Kielland, and Ibsen which I defend against Hamsun’s malicious argumentation. In the final part of the paper På turné is assessed with regard to the ways of how Hamsun’s oeuvre has evolved in time. This approach enables one to grasp some of På turné paradoxes, e.g.: the discrepancy between Hamsun’s early literary stance (neo-romanticism and militant, anti-bourgeois views) and the shape his work assumed later on (didacticism, the tendency to morally judge his heroes, support for the vulgar ideology of fascism, etc.).